THE IMPLEMENTATION OF PROJECT BASED LEARNING IN COURSEBOOK EVALUATION CLASSROOM - Yanuarti Apsari; Ida Lisdawati; Euis Rina Mulyani (Jurnal Ilmiah P2M STKIP Siliwangi, 2019)
Critical thinking is a crucial skill that university students need to develop. Project-based learning can be used to promote students’ critical thinking. The paper investigates the implementation of project based learning in Coursebook Evaluation course at a university setting. The purposes of this research study were: 1) to describe the implementation of Project based learning in Coursebook evaluation classroom and 2) to investigate the students’ difficulties during the implementation of Project based learning. The design of the research was descriptive qualitative. The subjects were the fourth semester students who were taking course book evaluation. The data were collected through observation, interview and students’ project. The findings showed that the implementation Project-Based Learning in Coursebook Evaluation class are through the following steps: (1) Discussing the materials about Course Book Evaluation, (2) working with the group in evaluating English Course Book, (3) creating the paper, (4) creating the video, and (5) presenting the video product. Moreover, the data from interview also revealed that there were three problems encountered by the respondents during the implementation of project based learning: finding appropriate information, writing the paper and creating the video.